Pengaruh Persepuluhan Terhadap Pertumbuhan Kesejahteraan Jemaat Di Gereja Bethany Indonesia 'Almasih Qom' Surabaya - Stanley Stanley; Wasidi Sugianto; Tantra Lingga Weinardy; Christian Eliazar Bawias; Andre Yulius (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2018)
This research was conducted to determine the effect of tithing on the growth of the welfare of the congregation. Tithing is the return of God to all the blessings that Christians have received. God's promise if tithing is done then the rest (90%) of God will be sanctified and God's blessings will be poured out more for Christians. Therefore from giving tithes increases the welfare of the congregation or believers. This study uses a quantitative method and data management techniques using simple linear regression with the help of the SPSS program. The results of the study show that tithing affects the welfare of the congregation.